Comparison of anti-fouling surface coatings for applications in bacteremia diagnostics - Boardman, Anna K. (2013)
To accurately diagnose microbial infections in blood, it is essential to recover as many microorganisms from a sample as possible. Unfortunately, recovering such microorganisms depends significantly on their adhesion to the surfaces of diagnostic devices. Consequently, we sought to minimize the adhesion of methicillin-sensitive Staphylococcus aureus (MSSA) to the surface of polypropylene- and acrylic-based bacteria concentration devices. These devices were treated with 11 different coatings having various charges and hydrophobicities. Some coatings promoted bacterial adhesion under centrifugation, whereas others were more likely to prevent it. Experiments were run using a simple buffer system and lysed blood, both inoculated with MSSA. Under both conditions, Hydromer’s 7-TS-13 and Aqua65JL were most effective at reducing bacterial adhesion.